Dairy cattle husbandry - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1996)
Dairy cattle husbandry Agrodok series No 14 by P Bonnier, A Maas and J Rijks available from CTA